2019
DOI: 10.1002/ece3.4952
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics of rapidly invading lionfish in the Caribbean reveals signals of range expansion in the absence of spatial population structure

Abstract: Range expansions driven by global change and species invasions may have significant genomic, evolutionary, and ecological implications. During range expansions, strong genetic drift characterized by repeated founder events can result in decreased genetic diversity with increased distance from the center of the historic range, or the point of invasion. The invasion of the Indo‐Pacific lionfish, Pterois volitans, into waters off the US East Coast, Gulf of Mexico, and Caribbean Sea provides a natural system to st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 76 publications
3
33
2
Order By: Relevance
“…Although it is known that populations that present a recent bottleneck show apparent excess of heterozygotes (Cornuet & Luikart, ; Sakai et al, ), our analyses found heterozygosis in all loci; therefore, it is likely to be a reflection of the founder effect noted in other studies (Freshwater et al, ). Even so, this information differs with the studies of Pérez‐Portela et al () and Bors et al (). However, the differences may be inherent to the different molecular markers used.…”
Section: Discussioncontrasting
confidence: 88%
“…Although it is known that populations that present a recent bottleneck show apparent excess of heterozygotes (Cornuet & Luikart, ; Sakai et al, ), our analyses found heterozygosis in all loci; therefore, it is likely to be a reflection of the founder effect noted in other studies (Freshwater et al, ). Even so, this information differs with the studies of Pérez‐Portela et al () and Bors et al (). However, the differences may be inherent to the different molecular markers used.…”
Section: Discussioncontrasting
confidence: 88%
“…Population genomic approaches, in particular, restriction siteassociated DNA sequencing (RADseq) (Miller et al, 2007;Baird et al, 2008;Peterson et al, 2012), offer a cost-effective solution for surveying genome-wide single nucleotide polymorphism (SNPs) in species without a sequenced genome. These techniques have proven useful to understanding species' invasion histories (Dupuis et al, 2018;Leydet et al, 2018;Bors et al, 2019;Cohen and Privman, 2019) and as a non-destructive method for identification and monitoring (reviewed in Taylor and Gemmell, 2016). More generally, emergence of RAD-based techniques have led to wide adoption of these methods in ecological and evolutionary studies of insects (Bagley et al, 2017;Storer et al, 2017;Lower et al, 2018;Zhang et al, 2018;De Jesús-Bonilla et al, 2019), including ants (Moreau and Wray, 2017;Boyle et al, 2018;Avril et al, 2019;Smith et al, 2019), which rank among the most damaging and difficult to control invasive species (Rabitsch, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we focused on the use of massively parallel genomic sequencing methods. The development and continued technological innovation of these tools have helped scientists answer expanding sets of questions in species biology, evolutionary history, behavioural ecology and population dynamics [8][9][10][11]. The genetics and genomics community as a whole has been a leader in the data sharing movement, with standardly used online repositories including the National Center for Biotechnology Information's Sequence Read Archive (SRA), the Gene Expression Omnibus and GenBank [12].…”
Section: Introductionmentioning
confidence: 99%